Pengaruh Pengembangan Karier dan Motivasi terhadap Kinerja Pegawai pada Badan Penanggulangan Bencana Daerah Kabupaten Tulang Bawang Barat - Umar Bakti; Desmon Desmon; Muhammad Habib Munandar (Business and Enterpreneurship Journal (BEJ), 2020)
This study aims to test the theory or hypothesis in order to determine the effect of the influence of career development and motivation on employee performance in the disaster management agency of the western onion bone district. The research carried out is a type of explanatory research. The results of this study indicate that there is an influence of career development (x1) on employee performance (y), with a level of influence (r-square) of 49%, which means career development has an effect of 49% on employee performance. there is an influence between work motivation (x2) on employee performance (y), with a level of influence of 35.2% which means that work motivation provides an influence of 35.2% on employee performance and there is an influence between career development (x1), work motivation (x2) with employee performance (y), with a level of influence of 50.7% which means that career development and work motivation gives an effect of 50.7% on employee performance.